Major ion chemistry of shallow groundwater in Khaliviin gol, Umnugovi province - D. Altantungalag (Geological Issues, 2023)
A hydrogeochemical study was conducted in the Khaliviin gol, Umnugovi province, to assess chemical composition of shallow groundwater and 27 groundwater samples were collected from different herder wells to monitor the water chemistry of various ions. Samples were collected in plastic polyethylene bottles for physicochemical analysis as well as all of the samples were analyzed in the laboratory of the Khanlab. Ca2+, Mg2+, Na+, K+, CO32-, HCO3-, Cl-. SO42- , and NO3- are carried out. This paper investigated the major ion chemistry of shallow groundwater in the area with two different methods such as statistical analysis, tri-linear diagrams. The water quality for drinking purposes was also assessed comparing with standards of National and World Health Organization. The concentrations of major ions were relatively lower in the upstream than downstream of shallow groundwater in the area, indicating from good to moderate water quality. The hydrochemical facies of the shallow groundwater in the study area are dominantly Na-HCO3-Cl, Na-Ca-HCO3, Ca-HCO3-SO4 and Na-Ca-HCO3 types. The chemical composition of the aquifer in the study area is related to rock-forming minerals and hydrochemical processes. It is confirmed by the result of correlation matrix. The main hydrochemical process in this aquifer is dissolution of the. halite, gypsum, calcite and dolomite. Moreover, increasing and decreasing number of some ions can be explained local recharge from precipitation.